2013
DOI: 10.1093/bioinformatics/btt755
|View full text |Cite
|
Sign up to set email alerts
|

MSIsensor: microsatellite instability detection using paired tumor-normal sequence data

Abstract: https://github.com/ding-lab/msisensor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
566
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 662 publications
(570 citation statements)
references
References 7 publications
2
566
0
2
Order By: Relevance
“…Microsatellite instability (MSI) was assessed for patients with HER2-mutant tumours with matched germline DNA sequencing data (n=89) using an orthogonal bioinformatics tool, MSIsensor 48 . Additionally, mutations were decomposed into the thirty constituent mutational signatures as described previously 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Microsatellite instability (MSI) was assessed for patients with HER2-mutant tumours with matched germline DNA sequencing data (n=89) using an orthogonal bioinformatics tool, MSIsensor 48 . Additionally, mutations were decomposed into the thirty constituent mutational signatures as described previously 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we next sought to assign our CRC case to one of these two subtypes. We used the MSIsensor tool (Niu et al 2014), together with the Illumina WGS data described above, to measure microsatellites in our tumor and adjacent normal control tissues (Methods). The microsatellite mutation rate in our CRC sample (0.01%) was clearly within the MSS range (Niu et al 2014) and was well below the rates observed in tumors that have MSI phenotypes (3.5%-41%).…”
Section: Resultsmentioning
confidence: 99%
“…Using MSIsensor (Niu et al 2014), we determined the total number of somatically mutated microsatellites in our normal/tumor pair plus three control TCGA normal/tumor colorectal cancer pairs in which the microsatellite status was known (two MSS samples and one MSI sample) (The Cancer Genome Atlas Network 2012; data not shown). Cases with <3.5% of microsatellites somatically mutated are considered to have stable microsatellites (MSS), whereas cases with >3.5% of microsatellites somatically mutated are considered to have microsatellite instability (MSI).…”
Section: Microsatellite Assessment Using Msisensormentioning
confidence: 99%
“…In RTK-altered cases for which mismatch repair protein expression for MLH1, PMS2, MSH2, and MSH6 had not yet been performed, a C++ program called MSI-sensor (7) was used to analyze MSK-IMPACT sequencing data for microsatellite stable versus microsatellite instability–high (MSI-H) status.…”
Section: Methodsmentioning
confidence: 99%